2020
DOI: 10.1021/acs.analchem.0c02537
|View full text |Cite
|
Sign up to set email alerts
|

Combining In-Tip Reaction and Infrared Thermal Imaging for Fast and Portable Enthalpimetric Analysis

Abstract: In this work, the in-tip thermal infrared enthalpimetry (in-tip TIE) method is proposed for fast enthalpimetric analysis. In this method, the reactions inside the tips of a multichannel pipette were combined with temperature monitoring by an infrared camera. The filter paper was used inside the tips to retain reagents as solutions (wetted paper mode) or as solids (dried paper mode) to perform neutralization, redox, or precipitation reactions. The dried reagents inside the tips were obtained by oven drying a so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In this approach, he suggested that temperature monitoring by an infrared camera can be combined with the response within the suction head of a multichannel liquid dispenser. Among them, the filter paper can be used inside the suction head to retain the reagent as a solution or solid for neutralization, redox, or precipitation reactions [5]. Sousa et al proposed that infrared thermal (IRT) imaging is a medical imaging mode to study skin temperature in real time, which can provide useful diagnosis and monitoring information of directly or indirectly related diseases.…”
Section: Related Workmentioning
confidence: 99%
“…In this approach, he suggested that temperature monitoring by an infrared camera can be combined with the response within the suction head of a multichannel liquid dispenser. Among them, the filter paper can be used inside the suction head to retain the reagent as a solution or solid for neutralization, redox, or precipitation reactions [5]. Sousa et al proposed that infrared thermal (IRT) imaging is a medical imaging mode to study skin temperature in real time, which can provide useful diagnosis and monitoring information of directly or indirectly related diseases.…”
Section: Related Workmentioning
confidence: 99%
“…Addresses the opportunities achievable through the adoption of RPA-based infrared imaging technologies to add value to the social, economic, and environmental performance of photovoltaic systems. Oliveira et al proposed a tip thermal infrared enthalpy (in-tip TIE) method for fast enthalpy analysis [4]. In this method, the reaction within the tip of a multichannel pipette is combined with temperature monitoring by an infrared camera.…”
Section: Introductionmentioning
confidence: 99%